Latin Sources’ Information about the Mongols Related to Their Reconquest of Transcaucaisa » - Roman Hautala (Золотоордынское обозрение)
The author of this article tried to trace the evolution of the Mongols’ perception in Latin sources based on information about their military expansion in the Middle East.The first mention of the Mongols appear in Latin sources in 1221. According to these sources, the Mongol army, which accomplished a number of conquests in Central Asia, Persia, and Transcaucasia, consisted of baptized nomads. Latin authors asserted that at the head of this army stood a certain David, “king of the Indies”, which sought to help the Middle Eastern Christians and “liberate” Jerusalem from Muslim rule. Undoubtedly, the Latin sources meant by the “deeds of king David” the first western campaign of the Mongols led by Genghis Khan, which began in 1219 and was directed against the Central Asian sultanate of Khwarezm. These Latin sources were written at the time, when the troops of Genghis Khan had already conquered Khwarezmian territory in Central Asia and began military actions in Khorasan, while the separate divisions of the Mongols led by Jebe and Subedei invaded Transcaucasia and inflicted the first serious defeat to the Christian kingdom of Georgia. Later, however, a positive Mongols’ perception in the West began to gradually change. First of all, this change was affected by reports of the Georgian rulers expressing obvious doubts about former confidence that the Mongol army was entirely composed of Christians. Even greater impact had information about beginning of the Mongol re-conquest of Transcaucasia. An early report of the Patriarch of Jerusalem about the Mongol units’ appearance in Transcaucasia headed by Chormaqan noyan still reflected the hope for the Mongols’ adherence to the Christian faith. However, subsequent reports on the beginning of the Mongol conquest of Great Armenia radically changed European perceptions of the Mongols. Starting from 1236, Latin sources began to represent the Mongols as fiends trying to interpret their appearance in accordance with apocalyptic scenarios of popular eschatological writings.